Evaluasi Kualitas Kesiapan Belajar Online Mahasiswa Baru Program Studi Manajemen Dakwah IAIN Pontianak - Abdullah Syifa (Universitas Hamzanwadi, 2021)
IAIN of Pontianak Dakwah Management Study Program is currently doing online learning. The implementation is surely difficult, especially for the new students. They need to be prepared in following the online learning. This condition is attracting the interest to evaluate the preparation quality. The purpose of this research is to evaluate the preparation quality of online learning the new students in IAIN of Pontianak Dakwah Management Study Program using the quantitative approach. The population of this research is all students from in IAIN of Pontianak Dakwah Management Study Program. The sampling technique used in this research is the total-sampling, where all the populations are used as the sample of research. Data collecting use the instrument for online learning preparation scale. Data analysis is conducted in two stages, where the data analysed in percentage quantitative descriptive and comparison with achievement category criteria. The results of this research show the median value of confidence dimension in using computer or the Internet for learning is 8,77. Median value for independent learning is 17,77. 8,95 are for students’ control dimension in the online-context. The learning motivation dimension in the online-context with 14,41 value, and confidence dimension in communicating online is 10,28 value.